Study of component features of essential oils of Rosmarinus officinalis and Salvia sclarea of Crimean origin - R. E. Ermachenkov; A. L. Markov; M. M. Agaev; E. V. Burtseva; I. I. Terninko (Разработка и регистрация лекарственных средств)
Introduction. Chromatographic profiling is the most efficient way to authenticate essential oils, the key limitation of which is the number of chromatographic profiles developed. The profiling methodology allows to take into account the geographical variability of essential oils by differentiating the profile into essential oilseed growing zones. Despite the presence of developed chromatographic profiles at the moment there is no information about the possible geographical variability of the demanded essential oils of clary sage and rosemary, obtained from local essential oilseed raw materials.Aim. Comparative study of the component composition of essential oils of clary sage and rosemary produced from raw materials of Russian and foreign origin for the characterisation of domestic essential oils.Materials and methods. The essential oils were analysed on the software and hardware complex of the gas chromatograph "Crystal 5000.2" with flame ionisation detection. Separation was carried out on a capillary column HP-5MS UI and on a capillary column DB-WAX. The components were identified by comparing the calculated linear retention indices obtained on two columns of different polarity with reference values.Results and discussion. The analysis of the essential oils of clary sage and rosemary identified 42 and 33 compounds, on average representing 93.7 and 96.2 % of all sample components, respectively. For the samples of clary sage of Crimean origin, a number of patterns were noted, potentially suitable for separating its component composition from essential oils of other origin. Based on the study of the component composition of the essential oil of rosemary Crimean origin, it is suggested that it is attributed to the essential oil of rosemary Spanish type in accordance with ISO and Ph.Eur.Conclusion. The results of the study allowed to put forward a number of assumptions regarding the possibility of isolation of a specific chromatographic profile of essential oils of clary sage and rosemary from Crimea. Further experimental verification of the put forward assumptions will allow to determine the possibility of introducing clear classification criteria for oils of Crimean origin.